Prevalence of Eosinophilic Esophagitis in Patients with Upper GI Symptoms in a Tertiary Care Center in North India - Mittal, Akshit; Seth, Saksham; Yadev, Sumit; Jain, Mukesh; Gupta, Gourav; Nijhawan, Sandeep (Journal of Digestive Endoscopy, 2025)
Eosinophilic esophagitis (EoE) is an emerging chronic immune-mediated esophageal disease characterized by eosinophilic infiltration of the esophageal mucosa. In India, the prevalence and predictors of EoE in patients presenting with gastroesophageal reflux symptoms remain inadequately explored. This article determines the prevalence of EoE in adult patients with esophageal symptoms and identifies potential clinical, endoscopic, and hematologic predictors of EoE.A prospective observational study was conducted at a tertiary care gastroenterology outpatient clinic between April 2023 and December 2024. Consecutive adult patients presenting with esophageal symptoms underwent esophagogastroduodenoscopy with targeted esophageal biopsies. Histopathological examination for mucosal eosinophilia (≥ 15 eosinophils per high-power field) was performed. Demographic, clinical, hematologic, and endoscopic parameters were analyzed to identify predictors of EoE.Among 350 screened patients, 4 (1.14%) were diagnosed with EoE. EoE patients were predominantly male with a mean age of 39.6 ± 4.2 years and had a higher prevalence of allergic history (75%) compared with non-EoE subjects (5.2%, p = 0.003). Nonresponse to proton-pump inhibitors (PPIs) was significantly associated with EoE (p = 0.001). Peripheral absolute eosinophil counts were elevated in EoE cases (median 410/mm3) compared with non-EoE cases (median 162/mm3, p = 0.02). Endoscopic features such as esophageal rings and linear furrows were noted in some EoE cases. Multivariate analysis identified allergy history and PPI nonresponsiveness as significant independent predictors of EoE.The prevalence of EoE among Indian adults with esophageal symptoms is low (1.14%). However, a personal history of allergy, elevated peripheral eosinophil count, and poor response to PPI therapy are significant predictors of EoE. Early recognition of these factors can facilitate targeted biopsy and accurate diagnosis of EoE in clinical practice.
Keywords: eosinophilic esophagitis; esophageal biopsy; gastroesophageal reflux